Comparative low-velocity impact behavior of bio-inspired and conventional sandwich composite beams. (8th September 2017) - Abo Sabah, S.H.; Kueh, A.B.H.; Al-Fasih, M.Y.
Abstract: A novel woodpecker's head-inspired sandwich beam, comprising carbon fiber laminated skins with rubber and aluminum honeycomb cores, was developed for low-velocity impact behavior improvement. A comparative study against conventional sandwich beam was performed employing three impact energy levels (7.28 J, 9.74 J, 12.63 J) by means of experimental and numerical methods. In all cases, bio-inspired beams were consistently superior to those conventional, with low developed stress, deformation, and damage area while carrying higher maximum impact force. Even with a low added mass, the impact resistance efficiencies of the bio-inspired beams were 2.7–5.7 times greater than those of conventional configuration, thus exhibiting an improved impact performance of the developed bio-inspired beam useful for future protection strategy.